Nitric oxide‐mediated cutaneous microvascular function is impaired in polycystic ovary sydrome but can be improved by exercise training. (22nd February 2013) - Sprung, V. S.; Cuthbertson, D. J.; Pugh, C. J. A.; Daousi, C.; Atkinson, G.; Aziz, N. F.; Kemp, G. J.; Green, D. J.; Cable, N. T.; Jones, H.
Key points Polycystic ovary syndrome (PCOS) is associated with cardiovascular disease. Nitric oxide (NO) is a naturally occurring molecule that possesses anti‐atherogenic properties. The contribution of NO to the dilatation of microvessels in the skin is currently unknown in women with PCOS. In this study, it was found that women with PCOS display impaired NO bioavailability compared with obese matched control women. Exercise training improves the microvascular dysfunction displayed in women with PCOS, via the upregulation of NO. These findings suggest exercise training can be a preventive strategy in women with PCOS. Abstract Polycystic ovary syndrome (PCOS) is associated with cardiovascular disease. The contribution of the nitric oxide (NO) dilator system to cutaneous endothelial dysfunction is currently unknown in PCOS. Our aim was to examine whether women with PCOS demonstrate impaired cutaneous microvascular NO function and whether exercise training can ameliorate any impairment. Eleven women with PCOS (age, 29 ± 7 years; body mass index, 34 ± 6 kg m−2) were compared with six healthy obese control women (age, 29 ± 7 years; body mass index, 34 ± 5 kg m−2). Six women with PCOS (30 ± 7 years; 31 ± 6 kg m−2) then completed 16 weeks of exercise training. Laser Doppler flowmetry, combined with intradermal microdialysis of l‐NG‐monomethyl‐l‐arginine, a nitric oxide antagonist, in response to incremental local heating of the forearm was assessed in women with PCOS and control women, and again in women with PCOS following exercise training. Cardiorespiratory fitness, homeostasis model assessment for insulin resistance, hormone and lipid profiles were also assessed. Differences between women with PCOS and control women and changes with exercise were analysed using Student's unpaired t tests. Differences in the contribution of NO to cutaneous blood flow [expressed as a percentage of maximal cutaneous vasodilatation (CVCmax)] were analysed using general linear models. At 42°C heating, cutaneous NO‐mediated vasodilatation was attenuated by 17.5%CVCmax (95% confidence interval, 33.3, 1.7; P = 0.03) in women with PCOS vs. control women. Exercise training improved cardiorespiratory fitness by 5.0 ml kg−1 min−1 (95% confidence interval, 0.9, 9.2; P = 0.03) and NO‐mediated cutaneous vasodilatation at 42°C heating by 19.6% CVCmax (95% confidence interval, 4.3, 34.9; P = 0.02). Cutaneous microvascular NO function is impaired in women with PCOS compared with obese matched control women but can be improved with exercise training.